2005
DOI: 10.1111/j.1523-1755.2005.00745.x
|View full text |Cite
|
Sign up to set email alerts
|

Increase in heme oxygenase-1 levels ameliorates renovascular hypertension

Abstract: These findings define an action of prolonged HO-1 induction to interrupt and counteract the influence of the renin-angiotensin-aldosterone system (RAAS) to increase in blood pressure in the 2K1C model of renovascular hypertension. Multiple mechanisms include a decrease in oxidative stress as indicated by the decrease in cellular heme and nitrotyrosine levels, an anti-inflammatory action as evidenced by a decrease in COX-2 and PGE2, interference with the action of angiontensin II (Ang II) as evidenced by an inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
82
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 103 publications
(94 citation statements)
references
References 64 publications
11
82
1
Order By: Relevance
“…[4][5][6][7][8][9] Despite these results, the mechanism by which systemic induction of HO-1 lowers blood pressure is not known. We have previously shown that kidney-specific induction of HO-1 through renal medullary interstitial infusion of cobalt protoporphyrin attenuates the development of Ang II-dependent hypertension.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…[4][5][6][7][8][9] Despite these results, the mechanism by which systemic induction of HO-1 lowers blood pressure is not known. We have previously shown that kidney-specific induction of HO-1 through renal medullary interstitial infusion of cobalt protoporphyrin attenuates the development of Ang II-dependent hypertension.…”
Section: Discussionmentioning
confidence: 91%
“…[4][5][6][7][8][9] Recently, we reported that kidney-specific induction of HO-1 by renal medullary interstitial infusion of cobalt protoporphyrin attenuated the development of angiotension II (Ang II) -dependent hypertension. 10 Although that work was the first to report that renal-specific induction of HO-1 could attenuate Ang II-dependent hypertension, the importance of vascular versus tubular induction of HO-1 could not be distinguished in this model.…”
mentioning
confidence: 99%
“…Therefore, these results would be more consistent with what's observed in hypertensive patients. Previous studies have observed no change in blood pressure during insulin pretreatment (Johansson et al 2008) and a decrease in blood pressure during heme induction (Botros et al 2005). Differences in previous studies could be attributed to the class, dose and/or type of administered agent in the study.…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies have demonstrated that hyperexpression of HO-1 by genetic or pharmacologic approaches may result in a relatively weak increase in cell HO activity, suggesting that much of the expressed protein is nonfunctional Quan et al, 2004;Teng et al, 2004;Botros et al, 2005). Quantification of activity may therefore be a more accurate index of the therapeutic potential of a drug or construct in a particular cell population than measurement of protein expression per se.…”
Section: Discussionmentioning
confidence: 99%